(2(x+2)/3)=5x-3

Simple and best practice solution for (2(x+2)/3)=5x-3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (2(x+2)/3)=5x-3 equation:


x in (-oo:+oo)

(2*(x+2))/3 = 5*x-3 // - 5*x-3

(2*(x+2))/3-(5*x)+3 = 0

(2*(x+2))/3-5*x+3 = 0

(2*(x+2))/3+(-5*3*x)/3+(3^2)/3 = 0

2*(x+2)-5*3*x+9 = 0

4-13*x+9 = 0

13-13*x = 0

(13-13*x)/3 = 0

(13-13*x)/3 = 0 // * 3

13-13*x = 0

13-13*x = 0 // - 13

-13*x = -13 // : -13

x = -13/(-13)

x = 1

x = 1

See similar equations:

| 4.8y=-3.36 | | -10n+12=-6n-4 | | 0.08+0.01(x+2)=-0.02(3-x) | | 2-y=12 | | -3=-(x+7) | | 7v^2-42=-35k | | -10=-2+12d | | -5=x/19-4 | | (2/15)x-(1/5)=1 | | 1-25q/4=-3q/4-1/2(5q+2) | | 20xz-35yz+4x-7y= | | -1=x-5/6 | | 19+h/-3=8 | | X-(-10)=21 | | 4x-7/5=x-5 | | 7y=14/3 | | 3/2x-6=0 | | (2/7)x+(4/7)=(-4/7) | | 7x-3(3+4x)=19 | | -x+5y=6 | | 5=x/6-3 | | 4(-1/4u+5/2)=4(7/2u+7/2) | | 3-5+4x=-12 | | 8x-6=-6 | | -3x+12=2x+2 | | 4(x+4)-2= | | 2.1(3+6z)=6.7+13z | | 2(a-4)=4a-(2d+4) | | a+2a+1/4a=180 | | 121x^2-2192x+4096=0 | | 3-8w-5v^2=2w | | 4-12=n+4 |

Equations solver categories